Taraxasterol repairs UVB-induced skin barrier injury through MAPK/NF-κB signaling pathways. Issue 1 (31st December 2022) - Zhang, Yuzhi; Fu, Hao; Zhang, Yongtao; Wang, Dongdong; Zhao, Dan; Zhang, Jiachan; Li, Meng; Wang, Changtao
ABSTRACT : Taraxasterol (TAL) is a pentacyclic triterpenoid compound, which has anti-inflammatory effect. Cytotoxicity assay was used to determine the optimal concentration of TAL and positive control dipotassium glycyrrhizinate (DG), and the optimal dose of UVB. Experimental data indicate that TAL has scavenging activity against UVB radiation-induced intracellular reactive oxygen species (ROS) compared to UVB controls. The contents of skin barrier-related factors in the groups were detected by Enzyme-linked immunosorbent assay (ELISA), then ELISA and quantitative polymerase chain reaction (qPCR) were used to detect changes in the inflammatory factors, apoptosis factors, and gene levels in the groups. Therefore, TAL stabilised the levels of inflammation, apoptosis, and skin barrier-related factors by regulating Mitogen-activated protein kinases/nuclear factor-k-gene binding (MAPK/NF-κB) signalling pathways, such as jun-amino-terminal kinase (JNK), p38, extracellular signal-regulated kinase (ERK), and NF-κB. These results suggest that TAL repairs UVB-induced skin barrier damage by scavenging reactive oxygen species and regulating the MAPK/NF-κB signalling pathway.